Changes in Follicular CD4+ T Helper Cells as a Marker for Evaluating Disease Progression in the Competition between HIV and Host Immunity - Wang, Xiaolei; Ziani, Widade; Xu, Huanbin (Frontiers in Immunology, 2016)
Follicular CD4+ T helper (TFH) cells interact with B cells in follicular germinal centers and play a prominent role in promoting effective humoral immune responses to pathogens, providing help for B cell development, and antibody affinity maturation. Recent studies indicate TFH cells are expanded in HIV/SIV chronic infection, or depleted in terminal stages of disease, yet relatively maintained in elite controllers when compared to uninfected controls. A better understanding of the mechanisms behind these immunologic abnormalities may lead to more effective vaccination and therapeutic strategies. Here we review recent findings of TFH cells in HIV/SIV infection, and discuss the correlation of changes and function of TFH cells with host immunity. Dysregulation or depletion of CD4+ TFH cells likely plays a major role in the inability of HIV infected patients to mount effective immune responses.